Pengaruh Sosial Media, City Branding dan City Image Terhadap Keputusan Berkunjung Wisatawan Di Daerah Sumba Barat - Wati, Rahma; Asiyah, Siti; Rachmadi, Kartika Rose (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine and analyze the influence of social media, city branding and city image on visiting decisions simultaneously or partially. This type of research is a quantitative approach with explanatory research. The object of this research is the Parijing traditional house tour located in West Sumba. The population in this study is the number of visitors to the traditional Parijing traditional house. The sample technique in this study was nonprobability sampling and was determined by purposive sampling. Determination of the sample in this study using the Malhotra formula and obtained a total sample of 80 respondents. Source of data in this study using primary data by distributing questionnaires to respondents. The results of this study are that social media, city branding and city image influence the decision to visit simultaneously. Meanwhile, partially social media influences visiting decisions, city branding influences visiting decisions and city image influences visiting decisions. Keywoard: Social Media, City Branding, City Image, Visiting Decisions